Progressive Muscle Relaxation: An adjuvant therapy for reducing pain and fatigue among hospitalized cancer patients’ receiving radiotherapy. - Pathak, Pragya; Mahal, Rajinder; Kohli, Adarsh; Nimbran, Vinod (International Journal of Advanced Nursing Studies, 2013)
Background: Cancer patients’ face number of problems, among those pain and fatigue are common problems. To manage pain and fatigue among cancer patients, studies now a days are even focusing on use of non-pharmacological/ non invasive methods as exercises, imagery etc. But studies on effect of progressive muscle relaxation (PMR) exercises on pain and fatigue among admitted patients are scarce. Objective: The study was done to evaluate effectiveness of PMR exercises on pain and fatigue among hospitalized cancer patients’ receiving radiotherapy. Methods: The study design was quasi-experimental Pre test Post test control group design. Total of 100 participants, 50 in each intervention and control group were included. The subjects in the intervention group received four PMR exercise sessions in 4weeks along with routine standardized treatment while subjects in control group received treatment as usual with no added intervention. Results: There was significant difference (p<0.01) in Pre NPRS (4.42±2.35) to post NPRS (3.44±2.05) scores among intervention group (PMR). Pre assessment mean fatigue scores (CFS) of subjects were 33.80±10.62 in intervention group (PMR) and 33.24±7.02 in controls where as post assessment CFS were 28.52±12.74 and 36.52±7.53 in intervention and control group respectively. There was significant (p<0.01) reduction in pre to post CFS in PMR group while fatigue increased significantly (p<0.01) in control group. Conclusion: PMR along with routine standard treatment is effective in reducing pain and fatigue among hospitalized cancer patients receiving radiotherapy.